KEANEKARAGAMAN MIKROALGA CHAROPHYTA DI SUNGAI MESAT KECAMATAN LUBUKLINGGAU TIMUR I KOTA LUBUKLINGGAU - Sepriyaningsih Sepriyaningsih; Harmoko Harmoko (Nusantara Hasana Berdikari, 2022)
This study aims to provide information about the diversity of Charophyta microalgae in the Mesat river, Lubuklinggau City. This type of research is survey research so that the data collection in this study was carried out by observation. This research was conducted in February-April 2020. The study was conducted in the Mesat River, samples of microalgae were taken from 3 different stations following the flow of the river. Based on the results of the research conducted, the Charophyta microalgae species found in the Mesat River, Lubuklinggau City, consisted of: 1 Class, 2 Orders, 3 Families, 10 Genus, 20 Species. Based on the analysis results, the diversity value at station 1 is 1.27, station 2 is 0.98 and station 3 is 1.04. while the dominance value at station 1 is 0.019, station 2 is 0.0008 and station 3 is 0.006. The uniformity value at station 1 is 0.42, station 2 is 0.32, and station 3 is 0.34. Measurement of abiotic factors in the Mesat river consists of: temperature, dissolved oxygen, acidity and brightness. The temperature at station 1 is 27.20C, station 2 is 26.56 0C and station 3 is 26.870C. The dissolved oxygen content at station 1 is 45.94 mg/L, station 2 is 42.31 mg/L, and station 3 is 44.63 mg/L. while the acidity at station 1 is 6.70, station 2 is 6.63 and station 3 is 6.6. Then the brightness of the Mesat river at station 1 is 16.33cm, station 2 is 22 cm and station 3 is 18.63cm. Microalgae diversity of the Charophyta division in the Mesat River, Lubuklinggau City in the Medium Category.